CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL PERFORMANCE AS DETERMINANTS OF FINANCIAL DISTRESS IN CONSUMER NON-CYCLICALS AND CYCLICAL FIRMS - Kesumo Wardhani, Nurhastuty; Pratama, Aditya Yoga; Emelia Sari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study aims to test and analyze the relationship and influence by using the independent variables, namely corporate governance and performance intellectual capital against financial difficulties. The corporate governance variable is measured by ACGIX, the performance variable intellectual capital is measured by total intangible assets, and financial distress is measured using the Beneish Z-Score. This study uses secondary data, namely annual financial reports. The sample used is the company consumer noncyclical and consumer cyclical listed on the Indonesia Stock Exchange in the period 2016 - 2021. The total sample selected was 260. The sampling technique used was purposive sampling. The method used in this research is panel regression analysis. The results of the analysis of this study indicate that corporate governance variables have a positive effect on financial difficulties, and performance variables intellectual capital have a positive effect on financial distress. It is hoped that this research can become a reference for further research as well as a basis for practitioners in making business decisions and for regulators to become the basis for making regulations in terms of the variables studied.